Developing a brief telematic cognitive behavioral therapy for the treatment of social isolation in young adults - Rossetti, Maria Gloria; Perlini, Cinzia; Girelli, Francesca; Zovetti, Niccolò; Brambilla, Paolo; Bressi, Cinzia; Bellani, Marcella (Frontiers in Psychology, 2024)
Objective The present study aims to present a novel cognitive-behavioral intervention protocol focused on treating social isolation through telematic interaction, thus overcoming common barriers characteristic of face-to-face interventions. Methods We examined current literature about face-to-face and telematic psychotherapeutic interventions for the treatment of social isolation in early adulthood. Current evidence is mixed, suggesting the need to develop novel interventions focused on patients’ cognitive functioning. Moreover, telematic interventions are promising candidates for overcoming common barriers intrinsic to the condition of social isolation. Results The present 8-session model inspired by cognitive behavioral theoretical models and cognitive interventions currently present in the literature is thought to help socially isolated adult patients reduce clinical symptoms associated with the condition and lead to a reduction in the avoidance of social situations, leading to an improvement of the quality of life. Conclusion We presented a telematic psychotherapeutic intervention aimed at helping adult patients suffering from social isolation who are unable to seek help from national health systems and face-to-face interventions, thus overcoming barriers intrinsic to social isolation. The present cognitive-behavioral treatment protocol has been developed in the context of a randomized clinical trial ongoing in Italy, aimed at implementing and testing the feasibility and effectiveness of multimodal digital interventions for treating social isolation.